Lateral gene transfer in evolution - Gophna, Uri (Springer New York, 2013)
Although the phenomenon of lateral gene transfer has been known since the 1940s, it was the genomics era that has really revealed the extent and many facets of this evolutionary/genetic phenomenon. Even in the early 2000s with but a handful of genomes available, it became clear that the nature of microorganisms is full of genetic exchange between lineages that are sometimes far apart. The years following this saw an explosion of genomic data, which shook the "tree of life" and also raised doubts about the most appropriate species concepts for prokaryotes. This book represents the manyfold contributions of LGT to the evolution of micro and, to an extent, macroorganisms by focusing on the areas where it has the largest impact: metabolic innovations and adaptations and speciation.